Induction of maturation of gold fish (Carassius auratus) using sesame seed extract (Sesamum indicum L. ) on feed as phytoestrogens - Handayani, Jullya Fratiwi; Farastuti, Eko Rini; Mumpuni, Sri Fia; Mulyana (Universitas Djuanda, 2024)
Gonad maturity in fish is essential in fish farming because it is related to seed production. Sesame oil is one of the ingredients as a feed supplement to stimulate fish gonad maturation. The research aimed to obtain the best dose of sesame seed extract (Sesamum indicum L.) in feed to increase the gonad maturity of comet fish (Carassius auratus). This research had four treatment levels and three repetitions. The treatment levels in this study were: P0 Without giving sesame seed extract (Control), P1 Giving sesame seed extract 5 mL/kg feed, P2 giving sesame seed extract 10 mL/kg feed, P3 Giving sesame seed extract 15 mL/kg. The results of the six-week study showed that at the beginning of maintenance, they were in TKG I, in the 3rd week, they entered TKG III, and in the 6th week, P1, P2, and P3 entered TKG IV while P0 were still in TKG III. The highest gonad maturity index at each observation time occurred in treatment P2 with feed containing 10 mL/kg of sesame seed extract. In the 1st week, the highest gonad maturity index occurred at P2 at 7.80. In the 3rd week, the highest gonad maturity index occurred in P2 at 9.26%. In the 6th week, the highest gonad maturity index occurred in P2 at 11.17%. Fecundity at week 6 showed the highest result of P2 4,290. The level of gonad maturity with treatment given sesame extract was faster, with a maintenance time of 6 weeks. The results of this study illustrate that sesame extract can be used as a supplement to increase comet fish gonad maturity.